1943
DOI: 10.1128/mmbr.7.1.43-56.1943
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of the Vi Antigen

Abstract: Typhoid fever is still a public health problem of considerable importance in many parts of the world. Any contribution to our fund of knowledge concerning the etiologic agent (applicable to diagnosis, prophylaxis, and therapy) is, therefore, to be welcomed as a possible basis for better control of the disease. The discovery by Felix and Pitt in 1934 (30, 31) of a hitherto undescribed antigenic component of the organism responsible for the disease was a step in this direction. Up to that time Eberthella typhosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1948
1948
1977
1977

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, the major weight of evidence presented by other workers is in favour of the reliability of such tests in the exclusion ofnon-carriers. This was first suggested by Felix et al (1935), and supported later by Pijper & Crocker (1937, 1938, Felix (1938), Bhatnagar (1938, Bensted (1940), Almon & Stovall (1940), Almon (1943, and others; although Horgan & Drysdale (1940), and Davis (1940), were less favourably disposed to the test because they found occasional Vi negative carriers, and were able to demonstrate raised Vi titres in subjects from whom the typhoid bacillus could not be isolated. A large-scale survey of this type in Egypt would certainly be of great value, for there is little doubt that the number of typhoid carriers among the 'fellahin' must be high.…”
Section: Discussionmentioning
confidence: 76%
“…However, the major weight of evidence presented by other workers is in favour of the reliability of such tests in the exclusion ofnon-carriers. This was first suggested by Felix et al (1935), and supported later by Pijper & Crocker (1937, 1938, Felix (1938), Bhatnagar (1938, Bensted (1940), Almon & Stovall (1940), Almon (1943, and others; although Horgan & Drysdale (1940), and Davis (1940), were less favourably disposed to the test because they found occasional Vi negative carriers, and were able to demonstrate raised Vi titres in subjects from whom the typhoid bacillus could not be isolated. A large-scale survey of this type in Egypt would certainly be of great value, for there is little doubt that the number of typhoid carriers among the 'fellahin' must be high.…”
Section: Discussionmentioning
confidence: 76%
“…These and subsequent results (table 3) also indicated that the capsular polypeptide is not an integral component of the cell wall or of other cell components. However, antiserum to cell walls (but not to wall polypeptide or, of course, the haptenic polysaccharide) reacted in high titer with encapsulated cells, allowing either of two interpretations: (a) Complete penetration of the capsule by antibody to cell walls is a first possi-1959] VENNES AND GERHARDT bility but seems unlikely, on the basis of findings by Schiutze (1932) and Almon (1943) that the presence of capsular material in other organisms prevents the reaction of antibody to somatic antigens, and by Tomesik (Spooner and Stocker, 1956) that incomplete penetration by capsular antibody is seen in capsules of B. megaterium.…”
Section: <3mentioning
confidence: 99%